Risks And Treats Of Broker Companies And How To Adress Them A Case Study In NTWO Company - Nafisi, Firooze (2009)
In this paper the author review brokerage companies and study the industry 's background and its characteristics, financial markets, FOREX history, FOREX traders and brokers, trading platforms, brokers' strategies, their risks and critical success factors.